1979
DOI: 10.1002/cpt1979265600
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of chlorimipramine and its demethyl metabolite during treatment of depression

Abstract: The biochemical and antidepressant effects of chlorimipramine (CI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(32 citation statements)
references
References 14 publications
3
29
0
Order By: Relevance
“…No significant effect of administration of benzodiazepine derivatives on desmethylation and hydroxylation of clomipramine was detected in the present study, which seems to be consistent with previous reports (Bertilsson et al 1988;Otani et al 1987;Traskman et al 1979). However, a more controlled study is necessary to clarify the matter because a few of the many kinds ofbenzodiazepines used in this study should not have been administered as they can be suspected to have interaction with metabolism of tricyclic antidepressants.…”
Section: Impact Of Administration Ofsupporting
confidence: 94%
See 2 more Smart Citations
“…No significant effect of administration of benzodiazepine derivatives on desmethylation and hydroxylation of clomipramine was detected in the present study, which seems to be consistent with previous reports (Bertilsson et al 1988;Otani et al 1987;Traskman et al 1979). However, a more controlled study is necessary to clarify the matter because a few of the many kinds ofbenzodiazepines used in this study should not have been administered as they can be suspected to have interaction with metabolism of tricyclic antidepressants.…”
Section: Impact Of Administration Ofsupporting
confidence: 94%
“…Although metabolic ratios for desmethylation corresponding to MRD in this study for various TCAs showed 9-to 15-fold variations for imipramine (Bnt,sen et al 1986a(Bnt,sen et al , 1986b, 5-fold variations for clomipramine (Traskman et al 1979), and 12-to 14-fold interindividual variations for amitriptyline (Bock et al 1982;Breyer-Pfaff et al 1982), respectively, Gram et al (1977) and Kuss and Jungkunz (1986) reported approximately 80-fold interindividual variations of desmethylation of imipramine and clomipramine, respectively. Approximately 36-fold interindividual variations in MRD were observed in our study.…”
Section: Interindividual Variations Of Desmethylation and Hydroxylatimentioning
confidence: 50%
See 1 more Smart Citation
“…Patients on neuroleptics or barbiturates as subordinate prescriptions were excluded because these drugs are known to alter the metabolism of tricyclic antidepressants (Alexanderson et al 1969;Daniel & Melzacka 1986;Krü ger et al 1986). Benzodiazepines in usual doses were permitted when patients complained of sleep disturbances or anxiety because these drugs do not substantially influence the metabolism of tricyclic antidepressants (Träskman et al 1979;Otani et al 1987;Bertilsson et al 1988). Patients with physical illness were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Cl is a fairly specific inhibitor of serotonin uptake (8), but when given to patients, demethylchlorimipramine (DMCI) is formed and accumulates to plasma concentra tions about twice those of the parent drug (17). As the metabolite is a potent inhibitor of nor adrenaline uptake, demethylation of Cl is an important determinant for the qualitative and quantitative biochemical effects during treat ment with the drug (23).…”
Section: Introductionmentioning
confidence: 99%